The dose-response relationship between training-load measures and changes in force-time components during a countermovement jump in male academy soccer players - Ellis, M.; Myers, T.; Taylor, R.; Morris, R.; Akubat, I. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To manage physical performance in soccer, practitioners monitor the training load (TL) and the resulting fatigue. A method frequently used to assess performance is the countermovement jump (CMJ). However, the efficacy of CMJ to detect fatigue from soccer matches and training remains uncertain, as does the relationship between TL and change in CMJ performance. The aims of the present study were 2-fold. One was to observe the changes of CMJ force-time components and jump height (JH). The second was to examine dose-response relationships between TL measures and CMJ over a 6-week preseason.